Environmental economics - Pearce, David W. (London ; New York : Longman, 1976)
This book sought to write in detail about the growth versus environment debate, the problems of estimating damage costs and control costs.
Includes index.
Bibliography: p. [192]-200.
aia 25/ 01/2019
Loans
Keywords: Environmental policy; Pollution; Conservation of natural resources